Instrumentation development for LASSII equatorial measurements - Trzcinski, Edmund; U.S. Air Force Geophysics Laboratory (Hanscom AFB, Massachusetts : Air Force Geophysics Laboratory, Air Force Systems Command, United States Air Force, 1980)
A quadrupole ion mass spectrometer capable of measuring ion composition during equatorial ionospheric irregularities with a spatial resolution of 4 m over a range of 1 to 56 AMU is discussed. Instrument sensitivity has been adjusted to cover an ion concentration range of 10 ions/cc to million ions/cc. A separate measurement of ion density and its fluctuations is also made. The instrument was developed to fly on a space-shuttle-launched LASSII satellite. (Author).
Research supported by the Air Force Geophysics Laboratory, Air Force Systems Command, United States Air Force, Hanscom AFB, Massachusetts.
Aeronomy Division Project 2310.
ADA088880 (from http://www.dtic.mil).
"23 April 1980."
Mode of access: Internet.
Keywords: Mass spectrometry; Ionosphere; Data reduction; Atmospheric physics; Ionosphere; Data reduction; Atmospheric physics; Mass spectrometry